Pengaruh Kepemimpinan Transformasional dan Kepuasan Kerja Terhadap Kinerja Guru SMK Mekanik Cibinong - Mohamad Hadisal Luthfi (Universitas Kristen Indonesia Toraja, 2024)
Transformational Leadership and job satisfaction have an important role in influencing the performance of teaching staff. Transformational leadership and satisfaction in its application are not only in improving teacher performance, but also in observing how teachers perform and meeting all the learning needs desired by students. The purpose of this research is to determine the influence of transformational leadership and job satisfaction on the performance of SMK Mekanik Cibinong teachers. The research method used is quantitative descriptive. The population of this study were teachers at SMK Mekanik Cibinong. Data collection methods using interviews, questionnaires, documentation and observation of data collection using questionnaires. Data processing uses the SPSS 20 application with multiple linear data analysis techniques. Based on the research results, it shows that transformational leadership has a significant influence on teacher performance and satisfaction also has a significant influence on teacher performance. Furthermore, transformational leadership and job satisfaction simultaneously have a significant influence on the performance of teachers at SMK Mekanik Cibinong.